Physico-chemical characterization of functional electrospun scaffolds for bone and cartilage tissue engineering. - Mouthuy, P; Ye, H; Triffitt, J; Oommen, G; Cui, Z (2010)
Mimicking the zonal organization of the bone-cartilage interface will aid the production of functional osteochondral grafts for regeneration of skeletal joint defects. This study investigates the potential of the electrospinning technique to build a three-dimensional construct recapitulating the zonal matrix of this interface. Poly(lactic-co-glycolic acid) (PLGA) and PLGA-collagen solutions containing different concentrations of hydroxyapatite nanoparticles (nHAp) were electrospun on a thin layer of phosphate buffer saline solution spread on the collector in order to facilitate membrane detachment and recovery. Incorporation of increasing amounts of nHAp in PLGA solutions did not affect significantly the average diameter of the fibres, which was about 700 nm. However, in the presence of collagen, fibres with diameters below 100 nm were generally observed and the number of these fibres was inversely proportional to the ratio PLGA:collagen and proportional to the content of nHAp. PLGA membranes were rather hydrophobic, although the aqueous drop contact angles progressively fell from 125 degrees to 110 degrees when the content of nHAp was increased from 0 per cent to 50 per cent (w/v). PLGA-collagen membranes were more hydrophilic with contact angles between 60 degrees and 110 degrees; the values being proportional to the ratio PLGA:collagen and the content of nHAp. Also, the addition of nHAp from 0 per cent to 50 per cent (w/v) in the absence of collagen resulted in decreasing dramatically both the Young's modulus (Ym), from 34.3 +/- 1.8 MPa to 0.10 +/- 0.06 MPa, and the ultimate tensile strain (epsilon max), from a value higher than 40 per cent to 5 per cent. However, the presence of collagen together with nHAp allowed the creation of membranes much stiffer, although more brittle, as shown for membranes made with a ratio 8:2 and 10 per cent of nHAp, for which Ym = 70.0 +/- 6.6 MPa and epsilon max = 7 per cent.